Effects of Poor Solid Waste Management on Faecal Sludge Emptying, Treatment and Disposal Services in Lusaka - Simwambi, Aubrey; Kapembwa, Mwila Angela; Kapanda, Kapanda (European Journal of Applied Sciences, 2023)
High urbanization rates but deficient basic service provision facilities in Zambian towns presents major challenges for municipalities in the collection, recycling, treatment and disposal of increasing quantities of produced human waste. Due to lack of proper functional systems for the management of solid waste in some Peri-urban areas (PUAs) of the city, some solid waste is disposed in some sanitation containment systems. Existing solid waste management practices in most PUA’s includes the throwing of waste in pit latrines. About 22 percent by weight of sludge emptied from latrines in Lusaka is solid waste. This solid waste possess negative effects on efforts to improve sanitation access for people in PUA’s; especially on the improvement of faecal sludge management(FSM) services from emptying to treatment and the end use or disposal of sludge products. This is because contained solid waste in sludge has made it difficult for pit-emptier’s and treatment plant operators to effectively empty and treat pit latrine sludge respectively due to cumbersome tasks of separating the waste from the sludge. Therefore, current methods for pit emptying remain mostly manual. Field performance tests on three pit latrine emptying technologies tested in Lusaka showed that none of the current innovative technologies offer any advantage over the currently used manual emptying methods (i.e. the use of an elongated scoopers). The failure of innovative pit emptying machines in sludge emptying entails there is need for households to stop current practices of waste management through disposal in pit latrines, otherwise proper sanitation services shall not be attained at household levels especially where need for emptying is required. The study explores the effects that solid waste presents on sanitation especially in FSM interventions from sludge emptying, treatment, reuse and disposal and recommends measures for FSM to have successful outcomes in accessible, affordable, and hygienic service provision.